Foregrounding Urban Agendas. The New Urban Issue in European Experiences of Policy-Making. - (:unkn) unknown (Springer, 2020)
This book highlights the discontinuities and the ongoing development of the urban question in policy-making in the context of the controversial current issues of global reversal and regional revival. It critically examines contemporary public policies and practices at the urban, regional and national scales in order to offer a timely contribution to the debate on the significance of the urban dimension and interpretation in terms of the theory, policy and practice of social-spatial research in the twenty-first century. Focusing on Europe, it explores the current urban policy agendas at different scales - and the mobility of those agendas -, their implications, contradictions and controversies. It brings together original contributions from multiple disciplines but with an urban perspective, including empirical case studies and critical discussions of the following topics: the UN 2030 Agenda for Sustainable Development, the global “New Urban Agenda” as part of the Habitat III process; the Urban Agenda for the European Union; national spatial policies related to urban agendas; urban agendas at regional/urban levels; city regionalism discourse and state rescaling; new formal regional and metropolitan governments as a solution (or problem); the role of new actors in regional urbanization dynamics; multi-level governance processes in developing an urban agenda; informal assemblages at the metropolitan scale aiming at constructing the urban concept and dimension.
Keywords: Stadtentwicklungspolitik; Nachhaltige Stadtentwicklung; Raumpolitik; Stadtregion; Planungsraum; Planungsebene; Urban Governance; Metropolregion; Regional Governance; Mehrebenenanalyse; Internationaler Vergleich; Fallstudie